Constraining Metaphor and Metonymy in Language and Depiction: A Cognitive Semiotics Approach - Zlatev Jordan (Studies in Logic, Grammar and Rhetoric)
In cognitive semiotics, metaphor and metonymy are crucially treated as special forms of sign use. In contrast, researchers in cognitive linguistics have extended the scope of metaphor and metonymy far beyond the traditional understanding of these semiotic figures based on, respectively, iconicity and contiguity into purely mental processes. I argue that this has led to unbounded over-extension, and general confusion about what metaphor and metonymy actually are, and thus on how to be able to reliably identify them in language and other semiotic systems like gesture and depiction. There is therefore an urgent need to constrain the concepts of metaphor and metonymy to more reasonable proportions, and in this article I propose such a more constrained approach, using the Motivation & Sedimentation Model (MSM) of meaning-making. For the purpose, I spell out an integrated definition of metaphor and metonymy along traditional lines, but not limiting them to language. I illustrate the applicability of this definition by offering analyses of political cartoons, showing how the two semiotic figures interact in complex ways, sometimes allowing for different interpretations.